Cellulose-derived carbon aerogels: A novel porous platform for supercapacitor electrodes. (July 2022) - Zhang, Chonghao; Wang, Haochen; Gao, Yanfeng; Wan, Caichao
Graphical abstract: Highlights: Summarize the preparation strategies of CDCAs from RCAs and NCAs. Analyze the role of hetero-atom doping in improving energy storage ability of CDCAs. Summarize the synergistic effect of CDCAs and integrated pseudocapacitive materials. Unveil the challenges and perspectives of CDCA-based electrodes and devices. Abstract: With the coming of the green chemistry era, the tunable porosity and superb environmental friendliness accompanied by outstanding electrical conductivity of cellulose-derived carbon aerogels (CDCAs) have remarkably promoted the development of high-performance green supercapacitor electrodes. In this review, a detailed overview on the preparation strategies of CDCAs and their precursors (regenerated cellulose aerogels and nanofibrillated cellulose aerogels) are presented. Two crucial approaches for the improvement of energy storage ability, i.e., hetero-atom doping and integration with pseudocapacitive materials, are summarized. Moreover, the role of CDCAs in the energy storage ability is analyzed from the view of structure–response relationship. A comprehensive overview of the fundamental aspects related to the configuration and energy storage mechanism of supercapacitors and the synthesis, structure, and property of cellulose is provided. Finally, this review presents a brief summary, challenges, and perspectives of CDCA-based supercapacitor electrodes and devices.